POTENTIAL DIVERSITY OF WATER ORGANISM AND WATER QUALITY OF THE LEBAK LEBUNG SWAMP ECOSYSTEM FOR FISHERIES IN RANTAU BAYUR DISTRICT, BANYUASIN REGENCY - Aisyah Fatriani; Hilda Zulkifli; Mochamad Syaifudin; Mohammad Rasyid Ridho; Dade Jubaedah (BIOVALENTIA: Biological Research Journal, 2022)
The abundance and diversity of aquatic organism and fish in Lebak Lebung Kemayan and Lebak Lebung Tudakan in Rantau Bayur District and their relationship to water quality in both of Lebak Lebung were researched in November 2021. The method used in determining the sampling location was "Purposive Sampling." Direct measurements in the field and sampling were carried out at station I, station II and station III in the two waters of Lebak Lebung. The results of the water quality analysis showed that the condition of the Lebak Lebung Kemayan and Lebak Lebung Tudakan swamp waters was classified as suitable for fishing activities (Government Regulation No. 82 of 2001). The average value of plankton and benthic diversity index was 2.34 and 1,86, the average uniformity index value was 0,85 and 0.95 (high) with a dominance index of 0.14 and 0.18 which indicated that there were no dominating plankton species and benthic. The value of the nekton diversity index ranges from 1,68-1,87 (average), the uniformity index value was between 0,47-0,73 (average-high) with a dominance index of 0,21-0,49 with the criteria that there were no dominating species nekton at this location. The results of the land suitability evaluation that waters Lebak Lebung in Rantau Bayur District are very suitable for fishing activities